A List of Linguistic Theses on Speech Therapy and Clinical Linguistics by the Iranian Students - MA Nasseh; B Yadegari; B Bakhtiari (Vesnu Publications, 2008)
Abstract Dissertations play an important role in progressing academic studies. In Iran unfortunately they remain unknown because of not having a comprehensive information system. This essay which is concluded from a broad research tries to introduce linguistic dissertations on Speech Therapy and then analyses its findings. Key words: Speech therapy, theses, aphasia, L1 acquisition, bilingualism